The mediating role of resilience in the relationship between meaning in life and attitude toward death among ICU nurses: a cross-sectional study - Wang, Lifang; Li, Sisi; Liu, Xiaorong; Li, Rong; Li, Ran (Frontiers in Psychology, 2024)
Background The majority of elderly individuals prefer to spend their final days in the Intensive Care Unit (ICU). ICU nurses are key providers in hospice care, and their attitudes toward death influence the quality of end-of-life nursing. Positive psychology emphasizes promoting positive attitudes toward death. A sense of meaning in life and resilience are critical aspects of positive psychology, which are essential for shaping ICU nurses’ attitudes toward death. Objective This study aims to investigate whether a sense of meaning in life indirectly affects attitudes toward death through the mediation of resilience. Method A total of 212 ICU nurses from four tertiary general hospitals in Guangdong and Fujian provinces, China, participated in this study. They completed an online questionnaire, including the Death Attitude Profile-Revised, the Connor-Davidson Resilience Scale, and the China Meaning in Life Questionnaire for ICU nurses. Results ICU nurses scored highest in natural acceptance (3.26 ± 0.53), followed by escaping acceptance (2.54 ± 0.59), and fear of death (2.53 ± 0.78). The proposed model fit the data well. Both the presence of meaning and the search for meaning were positive predictors of resilience (β = 0.313, p < 0.05; β = 0.256, p < 0.05). Resilience, the presence of meaning, and the search for meaning positively predicted natural acceptance (β = 0.299, p < 0.05; β = 0.294, p < 0.05; β = 0.177, p < 0.05). Conversely, these factors negatively predicted fear of death (β = −0.179, p < 0.05; β = −0.251, p < 0.05; β = −0.192, p < 0.05) and escaping acceptance (β = −0.208, p < 0.05; β = −0.208, p < 0.05; β = −0.219, p < 0.05). Mediation analysis indicated that resilience had a partial mediating role. Conclusion The presence of meaning and the search for meaning influence attitudes toward death, with resilience serving as a partial mediator. It is recommended that nursing administrators consider ICU nurses’ attitudes toward death and emphasize the importance of meaning in life and resilience in death education. This approach can help protect the psychological well-being of ICU nurses, promote a deeper understanding of life’s meaning, and develop a scientific perspective on death. Such measures are crucial for providing better humanistic care and psychological comfort to terminally ill patients and their families, thereby improving the quality of end-of-life care.